DMA, a bisbenzimidazole, offers radioprotection by promoting NFκB transactivation through NIK/IKK in human glioma cells. - Navrinder Kaur; Atul Ranjan; Vinod Tiwari; Ritu Aneja; Vibha Tandon (PLoS ONE, 2012)
Background Ionizing radiation (IR) exposure often occurs for human beings through occupational, medical, environmental, accidental and/or other sources. Thus, the role of radioprotector is essential to overcome the complex series of overlapping responses to radiation induced DNA damage. Methods and results Treatment of human glioma U87 cells with DMA (5- {4-methylpiperazin-1-yl}-2-[2'-(3, 4-dimethoxyphenyl)-5'-benzimidazolyl] in the presence or absence of radiation uncovered differential regulation of an array of genes and proteins using microarray and 2D PAGE techniques. Pathway construction followed by relative quantitation of gene expression of the identified proteins and their interacting partners led to the identification of MAP3K14 (NFκB inducing kinase, NIK) as the candidate gene affected in response to DMA. Subsequently, over expression and knock down of NIK suggested that DMA affects NFκB inducing kinase mediated phosphorylation of IKKα and IKKβ both alone and in the presence of ionizing radiation (IR). The TNF-α induced NFκB dependent luciferase reporter assay demonstrated 1.65, 2.26 and 3.62 fold increase in NFκB activation at 10, 25 and 50 µM DMA concentrations respectively, compared to control cells. This activation was further increased by 5.8 fold in drug + radiation (50 µM +8.5 Gy) treated cells in comparison to control. We observed 51% radioprotection in control siRNA transfected cells that attenuated to 15% in siRNA NIK treated U87 cells, irradiated in presence of DMA at 24 h. Conclusions Our studies show that NIK/IKK mediated NFκB activation is more intensified in cells over expressing NIK and treated with DMA, alone or in combination with ionizing radiation, indicating that DMA promotes NIK mediated NFκB signaling. This subsequently leads to the radioprotective effect exhibited by DMA.